Effect of Application of Several Organic Fertilizers on the Growth and Yield of Tobacco (Nicotiana Tabacum L.) - Ramadhan, Mohamad Aji Rizki; Subroto, Gatot; Arum, Ayu Puspita; Patricia SM, Susan Barbara (Journal of Soilscape and Agriculture, 2024)
Tobacco (Nicotiana Tabacum L.) is an agricultural commodity that is widely cultivated by the community. The decline in productivity is due to the uncontrolled use of chemical fertilizers and chemical pesticides, resulting in the degradation of organic matter. To deal with the problem can use Liquid Organic Fertilizer according to the dose for tobacco plants. The purpose of this study was to determine the effect of Liquid Organic Fertilizer treatment of shallot skin waste, banana stem waste, banana peel waste, and coconut coir waste on the growth and yield of tobacco plants. The study used a 1-factor Completely Randomised Design (CRD), with 5 levels, namely P0: Without Liquid Organic Fertilizer (Control), P1: Liquid Organic Fertilizer of shallot skin waste dose (300 ml/plant), P2: Banana stem waste Liquid Organic Fertilizer dose (300 ml/plant), P3: Banana peel waste Liquid Organic Fertilizer dose (300 ml/plant), P4: Liquid Organic Fertilizer ofcoconut fiber waste dose (300 ml/plant). The research variables observed included plant height, number of leaves, leaf length, leaf width, stem diameter, root length, root volume, wet weight of leaf production, and dry weight of leaf production. The effect of Liquid Organic Fertilizer application had a very significant effect on the variables of plant height, leaf length, leaf width, root length, leaf wet weight, and leaf dry weight. Coconut coir Liquid Organic Fertilizer treatment (P4) has a tendency to produce the best tobacco plant growth.